2001
DOI: 10.1084/jem.193.1.123
|View full text |Cite
|
Sign up to set email alerts
|

T Helper Cell Type 2 Cytokines Coordinately Regulate Immunoglobulin E–Dependent Cysteinyl Leukotriene Production by Human Cord Blood–Derived Mast Cells

Abstract: Human mast cells (hMCs) derived in vitro from cord blood mononuclear cells exhibit stem cell factor (SCF)-dependent comitogenic responses to T helper cell type 2 (Th2) cytokines. As cysteinyl leukotriene (cys-LT) biosynthesis is a characteristic of immunoglobulin (Ig)E-activated mucosal hMCs, we speculated that Th2 cytokines might regulate eicosanoid generation by hMCs. After passive sensitization for 5 d with IgE in the presence of SCF, anti-IgE–stimulated hMCs elaborated minimal cys-LT (0.1 ± 0.1 ng/106 hMCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
157
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 67 publications
9
157
2
1
Order By: Relevance
“…It remains to be determined whether STAT6 signaling is required to induce mast cells to release specific mediators that promote increased responsiveness to PGE 2 and histamine, or whether there is a separate, STAT6-dependent effect of IL-4 on intestinal epithelial cells that acts with a STAT6-independent mast cell effect to increase intestinal epithelial responsiveness. In support of the latter possibility, IL-4 has been shown to act through a STAT6-dependent mechanism to: 1) increase responsiveness to platelet-activating factor, histamine, 5-HT, and leukotriene C 4 in an anaphylaxis model (33,34); 2) induce increased expression of a receptor for cysteinyl leukotrienes (35); and 3) promote mast cell-dependent expulsion of Trichinella spiralis by infected mice through an effect on non-bone marrow-derived cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined whether STAT6 signaling is required to induce mast cells to release specific mediators that promote increased responsiveness to PGE 2 and histamine, or whether there is a separate, STAT6-dependent effect of IL-4 on intestinal epithelial cells that acts with a STAT6-independent mast cell effect to increase intestinal epithelial responsiveness. In support of the latter possibility, IL-4 has been shown to act through a STAT6-dependent mechanism to: 1) increase responsiveness to platelet-activating factor, histamine, 5-HT, and leukotriene C 4 in an anaphylaxis model (33,34); 2) induce increased expression of a receptor for cysteinyl leukotrienes (35); and 3) promote mast cell-dependent expulsion of Trichinella spiralis by infected mice through an effect on non-bone marrow-derived cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is modulating the expression and activity of the enzymatic components through transcriptional or posttranscriptional mechanisms. It has also been demonstrated that the nuclear import of 5-LO can modulate LT biosynthesis, because nuclear import of 5-LO can strongly enhance (48) or suppress (49) 5-LO activity. Recently, Flammand et al (50) have reported that PGE 2 and other cAMPelevating agents down-regulated LT biosynthesis by inhibiting 5-LO translocation to the nuclear envelope in human polymorphonuclear leukocytes (PMN).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from hMCs at 6-8 wk of culture with TRI Reagent (Molecular Research, Cincinnati), and RNA blotting was performed under high stringency conditions as previously described (23). For RT-PCR, RNA samples were primed with oligo(dT) and reverse transcribed in accordance with the manufacturer's protocol in an RT kit (CLONTECH).…”
Section: Methodsmentioning
confidence: 99%
“…When stimulated ex vivo by cross-linkage of their high-affinity Fc receptors for IgE (Fc RI), dispersed human lung MCs generate cys-LTs (22). When human MCs (hMCs), derived in vitro from cord blood, are primed with recombinant human IL-4 (10 ng͞ml), they express both the terminal biosynthetic enzyme, LTC 4 S, and Fc RI, thereby markedly up-regulating their generation of cys-LTs in response to Fc RI cross-linkage (23). Thus, the pivotal Th2 cytokine IL-4 regulates functions of MCs that are directly pertinent to their effector role in allergic inflammation.…”
mentioning
confidence: 99%